2015
DOI: 10.1111/zygo.12196
|View full text |Cite
|
Sign up to set email alerts
|

Language as a Values‐realizing Activity: Caring, Acting, and Perceiving

Abstract: A problem for natural scientific accounts, psychology in particular, is the existence of value. An ecological account of values is reviewed and illustrated in three domains of research: carrying differing loads; negotiating social dilemmas involving agreement and disagreement; and timing the exposure of various visual presentations. Then it is applied in greater depth to the nature of language. As described and illustrated, values are ontological relationships that are neither subjective nor objective, but whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…This research takes seriously the statements from van Lier (2004) and Hodges (2015) regarding the value-laden nature of language use and demonstrates a framework for understanding the moral ecology of language learning. The analysis revealed that participants evaluated their participation in unstructured speaking by appealing to certain moral reference points that guided their efforts to find good speaking opportunities.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This research takes seriously the statements from van Lier (2004) and Hodges (2015) regarding the value-laden nature of language use and demonstrates a framework for understanding the moral ecology of language learning. The analysis revealed that participants evaluated their participation in unstructured speaking by appealing to certain moral reference points that guided their efforts to find good speaking opportunities.…”
Section: Discussionmentioning
confidence: 96%
“…In Leo van Lier's (2004) discussion of an ecological perspective for language learning, he said that "there is no value-free or value-less language use" (p. 185). Steffensen and Kramsch (2017) repeated van Lier's statement and further referenced Bert Hodges (2015), who described "language as a valuesrealizing activity" (p. 712). These claims have deep implications for language learning research, but examples of empirical research that show what these implications are in practice have not yet materialized, even when similarly difficult and pivotal concepts have received increased attention from researchers in the past decade, such as agency (Brown, 2014;Jackson, 2011;Mercer, 2012;Xiao, 2014) or identity (Barkhuizen, 2017;Diao, 2017;Kinginger, 2015; see also Norton, 2013).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…5. Language realizes values by creating, pausing, and modifying intention and will (Hodges, 2015). 6.…”
Section: Orcid Idmentioning
confidence: 99%